Impact of Grazing on Soil Erosion in Forest Ecosystems - Singh, R. P.; Bahar, N.; Negi, D. V. (Indian Forester, 1995)
The effect of grazing on soil erosion in forest ecosystem was observed. It was seen that the grazed plot had approximately seven time more than soil loss per annum compared to ungrazed (control) plot under Cedrus deodara forest. The amounts of all the nutrients loss was recorded several times more in grazed plot than that of control. The amount of litterfall was recorded 3.3 times more annually in control stand corresponding to grazed stand.